Stable isotopes (δ^1^3C and δ^1?N) of microplankton collected during RV METEOR cruise M153 to the Benguela Upwelling System transit area - Bettina Martin; Rolf Koppelmann (PANGAEA, 2022)
Stable isotopes of d13C and d15N of two size fractions of microplankton were analyzed of samples taken during cruise M153 in February and March 2019 by an Apstein Net (20 μm mesh size). The sampling took place in the northern and southern Benguela upwelling system in the context of the project TRAFFIC (Trophic TRAnsfer eFFICiency in the Benguela Current). TRAFFIC aims to enlighten the energy transfer through the food webs of the northern and southern subsystems of the Benguela upwelling system. Stable isotopes help to determine the trophic level of organisms in the studied food web.